A multicenter cross-sectional study on proactive health knowledge, attitude, and practice and its influencing factors among resident standardized training physicians in Guangxi - Qian Zeng; Jichen He; Kun Ye; Xuepeng Du; Jianzhen Chang; Qiaoying Wei; Shenglin Liang (Frontiers in Public Health, 2026)
Objective The purpose of this study is to examine the state of proactive health knowledge, attitude, and practice (KAP) among Guangxi’s resident standardized training physicians as well as the factors that affect it. The results will be used to optimize health management strategies. Methods A multicenter cross-sectional survey was conducted. Univariate analysis was used to compare differences in proactive health KAP among residents with different characteristics, and multivariate linear regression was performed to identify associated factors. Results A total of 1,214 residents were included. The overall mean scores of proactive health knowledge, attitude, and practice were 4.32 ± 0.72, 4.40 ± 0.69, and 3.89 ± 0.64, respectively. Gender, household registration type, educational level, training identity, and region were significantly associated with KAP scores (all p < 0.05). Males had lower knowledge ( β = −0.239, p < 0.001) and attitude ( β = −0.183, p < 0.001) scores but higher practice scores ( β = 0.085, p < 0.05) than females. Residents with agricultural household registration had lower knowledge ( β = −0.124, p < 0.05) and attitude ( β = −0.126, p < 0.05) scores. Physicians from western and northern Guangxi had remarkably lower knowledge and practice scores ( p < 0.05); additionally, residents in northern Guangxi also obtained significantly poorer attitude scores ( β = −0.146, p < 0.05). Practice scores were higher in residents who were staff of the training base hospital ( β = 0.307, p < 0.05). Conclusion Standardized residents in Guangxi generally have sound proactive health knowledge and positive health attitudes. However, their practice score is markedly lower than the knowledge score and attitude score, which creates an obvious KAP gap. Obvious intergroup disparities exist in residents’ KAP levels. Targeted hierarchical health education should be carried out, with special attention paid to male residents, physicians with agricultural household registration, and practitioners in underdeveloped western and northern Guangxi, so as to bridge the gap between health cognition, positive attitudes and healthy behaviors.